Time to redefine endometriosis including its pro-fibrotic nature. Issue 3 (1st December 2017) - Vigano, P; Candiani, M; Monno, A; Giacomini, E; Vercellini, P; Somigliana, E
Abstract: Endometriosis is currently defined as presence of endometrial epithelial and stromal cells at ectopic sites. This simple and straightforward definition has served us well since its original introduction. However, with advances in disease knowledge, endometrial stromal and glands have been shown to represent only a minor component of endometriotic lesions and they are often absent in some disease forms. In rectovaginal nodules, the glandular epithelium is often not surrounded by stroma and frequently no epithelium can be identified in the wall of ovarian endometriomas. On the other hand, a smooth muscle component and fibrosis represent consistent features of all disease forms. Based on these observations, we believe that the definition of endometriosis should be reconsidered and reworded as 'A fibrotic condition in which endometrial stroma and epithelium can be identified'. The main reasons for this change are: (1) to foster the evaluation of fibrosis in studies on endometriosis pathogenesis using animal models; (2) to limit potential false negative diagnoses if pathologists stick stringently to the current definition of endometriosis requiring the demonstration of endometrial stromal and glands; (3) to consider fibrosis as a potential target for treatment in endometriosis. This opinion article is aimed at boosting the attention paid to a largely neglected aspect of the disease. We hope that targeting the fibrotic process might increase success in developing new therapeutic approaches.